Penerapan Metode Eksperimen pada Materi Fotosintesis pada Siswa SDN Mangli 01 Jember - Fika Afkarina; Muhammad Suwignyo Prayogo; Intan Azzahro; Dewi Kurniawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This research aims to determine the extent to which the application of a simple experimental method can help students understand the process of photosynthesis while also improving their learning outcomes. Based on field observations, some students appeared less active during the learning process and easily lost focus when learning was conducted solely thru the lecture method. Therefore, this research implements experimental-based learning activities so that students can be directly involved in the process of proving the concept. The research used a method involving two classes: IV A as the experimental group and IV B as the control group, each consisting of 29 students. Data was collected thru observation, interviews, documentation, and learning outcome tests. The data processing results showed a difference in outcomes between the pretest and posttest in both groups, with the experimental class achieving better learning outcome improvements. The t-test value of 32.470 with a significance level of 0.000 (p<0.05) confirms that the simple experimental method is capable of creating a more active learning environment, fostering learning interest, deepening understanding of photosynthetic concepts, and honing students' scientific thinking abilities and skills.